Optimising Agrivoltaic Systems: Identifying Suitable Solar Development Sites for Integrated Food and Energy Production - Apri Tri Nugroho; Sasongko Pramono Hadi; Heri Sutanta; Hyatma Adikara Ajrin (Journal of Power, Energy, and Control, 2024)
This study explores the integration of food and energy systems as a solution to address agricultural challenges in the dryland region of Gunungkidul Regency. Facing water scarcity issues, the region's abundant solar irradiation potential presents an opportunity for co-locating food and energy production, specifically through the implementation of an agrivoltaic system. Seven sub-districts had been designated in the local government regulations for solar energy development sites, including Gedangsari, Nglipar, Ngawen, Purwosari, Saptosari, Tanjungsari, and Tepus. Ten criteria and five constraints were established to assess their suitability for agrivoltaic systems. Utilising map overlay analysis and integrating GIS-MCDA with Fuzzy and AHP methodologies, three sub-districts—Semanu, Wonosari, and Tepus—emerged as the most suitable locations. Each sub-district boasts substantial total areas of 1,779.9 Ha, 1,325.5 Ha, and 1,147.21 Ha, respectively, with Tepus aligning with the local government's solar energy development plan. This comprehensive approach ensures that the selected locations meet both energy development goals and the potential for successful agrivoltaic implementation. In conclusion, this study demonstrates the feasibility of implementing food and energy combinations through an agrivoltaic system in Gunungkidul Regency, providing insights into suitable sub-districts and emphasising the importance of aligning regional energy plans with sustainable agricultural practices on arid land.